Reward, Context, and Human Behaviour - Clare L. Blaukopf; Gregory J. DiGirolamo (The Scientific World Journal, 2007)
Animal models of reward processing have revealed an extensive network of brain areas that process different aspects of reward, from expectation and prediction to calculation of relative value. These results have been confirmed and extended in human neuroimaging to encompass secondary rewards more unique to humans, such as money. The majority of the extant literature covers the brain areas associated with rewards whilst neglecting analysis of the actual behaviours that these rewards generate. This review strives to redress this imbalance by illustrating the importance of looking at the behavioural outcome of rewards and the context in which they are produced. Following a brief review of the literature of reward-related activity in the brain, we examine the effect of reward context on actions. These studies reveal how the presence of reward vs. reward and punishment, or being conscious vs. unconscious of reward-related actions, differentially influence behaviour. The latter finding is of particular importance given the extent to which animal models are used in understanding the reward systems of the human mind. It is clear that further studies are needed to learn about the human reaction to reward in its entirety, including any distinctions between conscious and unconscious behaviours. We propose that studies of reward entail a measure of the animal's (human or nonhuman) knowledge of the reward and knowledge of its own behavioural outcome to achieve that reward.